Collonization and Oviposition Preference of Six Weevil Species on Various Colors of Storage Container - Ludji Pantja Astuti; Rommy Parcelino Prabowo; Akhmad Rizali; Mutala'liah Mutala'liah (Jurnal Perlindungan Tanaman Indonesia, 2019)
Color preferences on post-harvest adult pests are useful for monitoring instrument development which based on the colonization and oviposition behavior. The research was aimed to determine the most attractive color with a certain wavelength for the test insects. The research was conducted in laboratory conditions of Plant Pest Laboratory, Department of Plant Pest and Disease, Faculty of Agriculture, University of Brawijaya at 27 ± 2°C, RH 65 ± 5%; and day:light 12:12 hours. Study of color preferences on six species of weevil used free choice test method and set by CRD with four replications using eight colors: white, red, orange, yellow, green, blue, indigo, and purple. The observed parameters were the number of adults and eggs laid. Results showed that each post-harvest insect had a different preference for various colors in the range of 380–450 nm wavelength. Adults of Sitophilus oryzae, Oryzaephilus surinamensis, O.s Mercator, and Tribolium castaneum were more preferred to feed and lay eggs in blue color (451–495 nm), Lasioderma serricorne was more preferred in indigo color (445–450 nm), and S. zeamais was more preferred in purple color (380–444 nm). The oviposition preference revealed that there was a positive correlation between the number of females and the egg laid.